La baja autoestima y su relación con el consumo de alcohol en los estudiantes del colegio Calasanz de la ciudad de Loja en el periodo enero-julio del 2014. - Iñiguez Luzuriaga, Viviana Estefanía (2015)
The present investigation was done to teenagers, that constitute a capable group in the company for the different physical, psychological and social, like that changes as the search of if same as persons inside the company, adopting such behaviors as the consumption of alcohol. In the present study were identified the cases of low self esteem by age and genre; the number knows of teenagers that consume alcohol in relation with the age and genre; to relate the low self esteem and the consume of alcohol; and to offer an educational design to the consciousness of the use of alcohol, for which it could descriptive and transverse investigation of type. The collection of information was realized in 146 students of first, second and third high school unified, morning section of the Unidad Educativa "Calasanz" through the application of surveys as the Test Rosenberg Self Esteem Scale and Alcohol Use Disorders Identification Test for the collection of information, concluding that low self esteem were presenting more frequently in the students, predominantly in males kind, and 17 years; 59% of the population consumes alcohol with more trend in males with 60% at the age of 17 years; and low self esteem is related to alcohol consumption in teenagers, because 72% of students with low self esteem consume alcohol. Finally, the following recommendations were made: tracking by the guidance department of the institution to students with characteristics of low self esteem; to organize workshops where is educated to parents about how to improve communication with their children to encourage their autonomy and independence; to foment activities in the school, promoting health and prevention of alcohol consumption and its consequences; and to realize additional investigations for early detection of alcohol consumption among teenagers. Keywords: Low self esteem, consume of alcohol, teenagers